Olhares, percepções e formações: as experiências dos mestrandos no Estágio Docência - Oliveira, Lécia Carneiro de (2025)
This dissertation analyzes the learning of university teaching that is woven through the relationship between professors and students in the Postgraduate Program in Education. The objective is to understand how master's students develop their learning of university teaching through the process of homology, that is, through the relationship they build with undergraduate professors when carrying out their internship and teaching. The concept of homology is conceived from the perspective of inspiration, a way of learning from others, which occurs in the daily coexistence of weaving the teaching profession. The study is anchored in the (auto)biographical approach, inscribed in the field of qualitative research, highlighting the place of relationships, dialogues, exchanges and sharing, which are fundamental for the understanding of research. Narrative interviews were chosen as the research device, which occupy the place of centrality of being and production of meanings that the subject himself constructs. Therefore, the narratives that are constituted in this research were subject to a comprehensive-interpretative reading based on Ricoeur (1996). The theoretical basis that supports this study refers to the studies of Bragança (2012), Conte and Pimenta (2015), Cunha (2010), Dubar (2006), Josso (2007), Larrosa (2002), Morosini (2000), Silva and Alves (2020), Silva (2020), Soares and Cunha (2010), Tardif (2002), among others. The categories present in this study reflect on the concepts of identity, teacher training, constitution of university teaching and the relationships between knowledge and experiences in postgraduate studies. As a result, it was evident that the internship is considered a formative locus. *The narratives predominantly reveal meaningful experiences grounded in positive, affective, and dialogical relationships with university professors. Thus, master’s students report that they develop their learning through engagement with others, in a dynamic process of acquiring knowledge through homology.* Furthermore, this work highlighted the need for emerging training in postgraduate courses, as there is no specific training to deal with university teaching practices, being considered a field of knowledge with gaps in its training process.